THE EFFECTIVENESS OF CLOZE TESTS IN ASSESSING THE SPEAKING/WRITING SKILLS OF UNIVERSITY EFL LEARNERS - Safarova, Mashhura Dilmurodovna (Innovative Development in Educational Activities, 2023)
This article investigates the effectiveness of cloze tests as a tool for evaluating the speaking and writing skills of university English as a Foreign Language (EFL) learners. Cloze tests, traditionally associated with reading comprehension, have been adapted to assess a range of language skills. The study explores the adaptability of cloze tests in evaluating oral proficiency through strategically designed audio recordings and their application in assessing writing skills by highlighting the construction of coherent and grammatically correct sentences.